Deposit insurance suitable for Europe: Proposal for a three-stage deposit guarantee scheme with limited European liability - Jan Pieter Krahnen (Goethe University Frankfurt, SAFE - Sustainable Architecture for Finance in Europe, 2013)
In this note, a new concept for a European deposit guarantee scheme is proposed, which takes account of the strong political reservations against a mutualization of the liability for bank deposits. The three-stage model for deposit insurance outlined in the text builds on existing national deposit guarantee schemes, offering loss compensation on a European level and at the same time preventing excessive risk and moral hazard taking by individual banks. – – In dieser Notiz wird ein neues Konzept für eine europäische Einlagensicherung vorgeschlagen, welches den starken politischen Vorbehalten Rechnung trägt, die gegen eine Vergemeinschaftung der Haftung für Bankeinlagen bestehen. Das skizzierte drei-stufige Einlagensicherungsmodell führt existierende nationale Einlagensicherungseinrichtungen weiter, bietet einen europäischen Verlustausgleich und verhindert eine exzessive Risikoübernahme zu Lasten der internationalen Gemeinschaft.
urn:nbn:de:hebis:30:3-314057
Keywords: 330; banking union; deposit insurance; bank risk